Women and Men in Jail: Attitudes Towards and Experiences of Domestic Violence - Ventura, Lois A. (American journal of criminal justice, 2007)
This study explores the pre-arrest domestic violence victimization and attitudes towards domestic violence reported by women and men confined in a Midwestern metropolitan jail. Results indicated that women in the jail sample had more fear for the safety of battered women than men in the jail sample. Women in jail were more likely than men in jail to view the legal system as a deterrent to domestic violence. Logistic regression models were constructed to explore associations between jail detainees’ pre-arrest experiences of domestic violence and their gender, age, education, race, parental status and other violent victimizations. The variables associated with pre-arrest domestic violence victimization were being a woman, a parent, a victim rape and a victim of threats with a deadly weapon.